2023
DOI: 10.1021/acs.est.3c00852
|View full text |Cite
|
Sign up to set email alerts
|

Ipso Substitution of Aromatic Bromine in Chlorinated Waters: Impacts on Trihalomethane Formation

Abstract: Parabens and salicylates were examined as disinfection byproduct (DBP) precursors to explore the possible influence of ipso substitution (i.e., halogen exchange) on the yield and speciation of trihalomethanes (THMs) formed during water chlorination. Substoichiometric conversion of C–Br bonds into C–Cl bonds was confirmed for several parabens and salicylates. The co-occurrence of (mono)­brominated and nonhalogenated precursors in the presence of free chlorine (but in the absence of added Br–) generated polybrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
2
0
0
Order By: Relevance
“…Compared to the reaction sequence between EOM and chlorine, aliphatic C–Cl groups and amide CO groups in Cu-EOM (formed by the binding of Cu­(II) and EOM) were preferentially reacted with chlorine to form DBP. Previous researches have shown that aliphatic compounds had higher TCM yield than aliphatic compounds without a chlorine atom . Therefore, the influence of Cu­(II) on DBP formation during chlorination was summarized as that the complexation of Cu­(II) and EOM fractions formed various binding ligands and altered their chloride reactivity, thus increasing the risk of DBP generated by EOM, which was consistent with a previous report that a hydroxyl group in aliphatic organic compounds conversed to a carbonyl group by the catalysis of Cu­(II) .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Compared to the reaction sequence between EOM and chlorine, aliphatic C–Cl groups and amide CO groups in Cu-EOM (formed by the binding of Cu­(II) and EOM) were preferentially reacted with chlorine to form DBP. Previous researches have shown that aliphatic compounds had higher TCM yield than aliphatic compounds without a chlorine atom . Therefore, the influence of Cu­(II) on DBP formation during chlorination was summarized as that the complexation of Cu­(II) and EOM fractions formed various binding ligands and altered their chloride reactivity, thus increasing the risk of DBP generated by EOM, which was consistent with a previous report that a hydroxyl group in aliphatic organic compounds conversed to a carbonyl group by the catalysis of Cu­(II) .…”
Section: Resultssupporting
confidence: 88%
“…Previous researches have shown that aliphatic compounds had higher TCM yield than aliphatic compounds without a chlorine atom. 43 Therefore, the influence of Cu(II) on DBP formation during chlorination was summarized as that the complexation of Cu(II) and EOM fractions formed various binding ligands and altered their chloride reactivity, thus increasing the risk of DBP generated by EOM, which was consistent with a previous report that a hydroxyl group in aliphatic organic compounds conversed to a carbonyl group by the catalysis of Cu(II). 44 These results also confirmed that the TCM yield in EOM increased with increasing Cu(II) concentration (Figure 1c).…”
Section: Dbp Formation During the Chlorination And Coppersupporting
confidence: 87%